Effect of neonatal thymectomy on immune responses of rats to Streptococcus mutans. - Ebersole, J L (1982)
The effect of neonatal thymectomy on secretory and systemic antibody responses in rats was studied. Groups of normal or thymectomized (Tx) rats were infected or immunized and infected with Streptococcus mutans 6715. Tx rats exhibited a significantly lower level of salivary immunoglobulin A (IgA) antibody to S. mutans after a 45- to 65-day infection. Similarly, after multiple local injections of formalinized S. mutans, Tx rats showed a delay in the appearance and lower levels of salivary IgA antibody to S. mutans. Serum IgG antibody levels were also decreased in Tx rats with both experimental protocols. In contrast, salivary IgG and serum IgM anti-S. mutans activity in Tx and normal rats were similar during the experiments. These results demonstrated that thymus deprivation at birth produces profound effects on the ability of rats to manifest secretory IgA antibody responses to the pathogenic microorganism S. mutans.